Disrespect and abuse of women during the process of childbirth in the 2015 Pelotas birth cohort - Marilia Arndt Mesenburg; Cesar Gomes Victora; Suzzane Jacob Serruya; Rodolfo Ponce de León; Andrea Homsi Damaso; Marlos Rodrigues Domingues; Mariangela Freitas da Silveira (BMC, 2018)
Abstract Background The disrespect and abuse of women during the process of childbirth is an emergent and global problem and only few studies have investigated this worrying issue. The objective of the present study was to describe the prevalence of disrespect and abuse of women during childbirth in Pelotas City, Brazil, and to investigate the factors involved. Methods This was a cross-sectional population-based study of women delivering members of the 2015 Pelotas birth cohort. Information relating to disrespect and abuse during childbirth was obtained by household interview 3 months after delivery. The information related to verbal and physical abuse, denial of care and invasive and/or inappropriate procedures. Poisson regression was used to evaluate the factors associated with one or more, and two or more, types of disrespectful treatment or abuse. Results A total of 4275 women took part in a perinatal study. During the three-month follow-up, we interviewed 4087 biological mothers with regards to disrespect and abuse. Approximately 10% of women reported having experienced verbal abuse, 6% denial of care, 6% undesirable or inappropriate procedures and 5% physical abuse. At least one type of disrespect or abuse was reported by 18.3% of mothers (95% confidence interval [CI]: 17.2-19.5); and at least two types by 5.1% (95% CI: 4.4-5.8). Women relying on the public health sector, and those whose childbirths were via cesarean section with previous labor, had the highest risk, with approximately a three- and two-fold increase in risk, respectively. Conclusions Our study showed that the occurrence of disrespect and abuse during childbirth was high and mostly associated with payment by the public sector and labor before delivery. The efforts made by civil society, governments and international organizations are not sufficient to restrain institutional violence against women during childbirth. To eradicate this problem, it is essential to 1) implement policies and actions specific for this type of violence and 2) formulate laws to promote the equality of rights between women and men, with particular emphasis on the economic rights of women and the promotion of gender equality in terms of access to jobs and education.